Andrea Fraser and the Psychoanalytic Character of Critique: From Normotic Performance to a Space of Play. (2nd April 2020) - Sykes, Rebecca
Abstract : This article will examine how the practice of critique is made vivid in the early performances of Andrea Fraser, the artist associated most conspicuously with Institutional Critique (IC), an umbrella term for a variety of critical artistic practices that developed out of the conceptual art movement of the 1960s. It traces the convoluted position of critique in contemporary art history, as distinct from literary studies, before discussing how academic art criticism privileges psychoanalytic models that articulate strong forms of negative critique at the expense of more affectively attuned and relational readings. Anderson's ( Bleak Liberalism, Chicago and London, 2016) discussion of the relationship between psychology and ideological analysis in literary criticism, in particular her elucidation of the characterological nature of the terms that recur in academic discourse, is used to introduce the ideas of British object relations into the sphere of contemporary art criticism: D. W. Winnicott's theory of creative play is used to make a 'playful' interpretation of Fraser's performance as the putative docent Jane Castleton in work like Museum Highlights: A Gallery Tour (1989). In comparison to critical accounts of this early work that stress the postmodernist 'character' of Jane as the ventriloquist of various ideological texts, this article explicitly acknowledges Fraser's presence as a charismatic performer in order to discuss how Jane's 'normotic personality', typified by 'the numbing and eventual erasure of subjectivity' (Bollas, The Shadow of the Object: Psychoanalysis of the Unthought Known, London, 1987), is an evocative enactment of the existential dimensions of critique.